PERAN PEKERJA SOSIAL DALAM KUALITAS HIDUP INDIVIDU DENGAN MULTIPLE DISABILITIES: ANALISIS BIBLIOMETRIK - Septiyani, Dhepita; Juliana, Elza Tri; Trustisari, Hastin (Triwikrama: Jurnal Ilmu Sosial, 2025)
This research focuses on a bibliometric analysis relating to the contribution of social workers in improving the quality of life of individuals with multiple disabilities. This analysis involves mapping scholarly publications as well as emerging research trends. The bibliometric data analyzed includes articles, journals, books, conferences, and other relevant documents. Through bibliometric analysis, it is hoped that accurate and objective information can be generated about the contribution of research in this field and how it can influence social workers' practice in the field. However, there is still a lack of studies that significantly explore the impact of social work interventions on the quality of life of individuals with multiple disabilities. This not only contributes to the academic literature, but also provides useful recommendations for practitioners and policy makers in improving the quality of life of individuals with multiple disabilities. Penelitian ini berfokus pada analisis bibliometrik yang berkaitan dengan kontribusi pekerja sosial dalam meningkatkan kualitas hidup individu dengan multiple disabilities. Analisis ini melibatkan pemetaan publikasi ilmiah serta tren penelitian yang muncul. Data bibliometrik yang dianalisis melalui artikel, jurnal, buku, konferensi, dan dokumen relevan lainnya. Melalui analisis bibliometrik, diharapkan dapat dihasilkan informasi yang akurat dan objektif mengenai kontribusi penelitian dalam bidang ini yang bertujuan bagaimana penelitian tersebut dapat mempengaruhi praktik pekerja sosial di lapangan. Namun, masih terdapat kekurangan studi yang secara signifikan mengeksplorasi dampak intervensi pekerja sosial terhadap kualitas hidup individu dengan multiple disabilities. Hal ini tidak hanya berkontribusi pada literatur akademik, tetapi juga memberikan rekomendasi yang bermanfaat bagi para praktisi dan pembuat kebijakan dalam meningkatkan kualitas hidup individu dengan disabilitas ganda.